2020
DOI: 10.1101/2020.05.22.20106476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of lockdown measures on COVID-19: a worldwide comparison

Abstract: Objective We aimed to determine which aspects of the COVID-19 national response are independent predictors of COVID-19 mortality and case numbers. Design Comparative observational study between nations using publically available data Setting Worldwide Participants Covid-19 patients Interventions Stringency of 11 lockdown policies recorded by the Blavatnik School of Government database and earliness of each policy relative to first recorded national cases Main outcome measures Association with log10 National de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 20 publications
(19 reference statements)
0
41
0
Order By: Relevance
“…The international Lockdown response has been meticulously documented by the Oxford University Government Response tracker[7] which consists of individual lockdown and economic policies scored on an ordinal scale and a composite lockdown score which measures the overall lockdown strength, on a daily basis, for almost every country in the world, a sizeable undertaking which has improved our understanding of the effectiveness of Lockdown strategies. [8] While the lockdown has been widely effective, it has come with substantial financial, social and political costs and exerted a heavy toll on the mental [9], [10] and physical health [11]—[13]of the population. Perpetual lockdown is widely deemed to be politically untenable, though a lockdown of some degree may be the only way of holding the disease back and reducing mortality while vaccine development is in progress.…”
Section: Introductionmentioning
confidence: 99%
“…The international Lockdown response has been meticulously documented by the Oxford University Government Response tracker[7] which consists of individual lockdown and economic policies scored on an ordinal scale and a composite lockdown score which measures the overall lockdown strength, on a daily basis, for almost every country in the world, a sizeable undertaking which has improved our understanding of the effectiveness of Lockdown strategies. [8] While the lockdown has been widely effective, it has come with substantial financial, social and political costs and exerted a heavy toll on the mental [9], [10] and physical health [11]—[13]of the population. Perpetual lockdown is widely deemed to be politically untenable, though a lockdown of some degree may be the only way of holding the disease back and reducing mortality while vaccine development is in progress.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggests that the implementation of behaviour interventions, specifically the lockdown, had a significant impact in reducing the peak and increasing the rate of declining cases. This appears in line with the effect of lockdowns to suppress the initial wave of COVID-19 community transmissions taken by countries such as China [23,24], and even on subsequent waves such as in Victoria, Australia [25], specifically international travel restrictions and workplace closure, which appears to reduce the R0 [26], rapidly bringing down the number of new and active cases of COVID-19, and reducing mortality [27].…”
Section: Resultsmentioning
confidence: 75%
“…Daon et al (2020) suggest that an additional prominent reason for the especially wide and rapid spread of COVID-19 is likely to be the current high prevalence of international travel 45 . According to Papadopoulus et al (2020) early international travel restrictions may help control the pandemic 46 , and Walch et al (2020) found that border closure had the potential of preventing cases 43 . For Chinazzi et al (2020) most of the imported cases outside China have likely originated from air travel 47 and Linka et al suggest that the spread of COVID-19 in Europe closely followed air travel patterns and that the severe travel restrictions implemented there resulted in substantial decreases in the disease’s spread 48 .…”
Section: Resultsmentioning
confidence: 99%
“…For Papadopoulus et al (2020) early introduction of these policies are of greater importance than its stringency. 46…”
Section: Resultsmentioning
confidence: 99%